The Road to Elimination: Current State of Schistosomiasis Research and Progress Towards the End Game - Ogongo, Paul; Nyakundi, Ruth K.; Chege, Gerald K.; Ochola, Lucy (Frontiers in Immunology, 2022)
The new WHO Roadmap for Neglected Tropical Diseases targets the global elimination of schistosomiasis as a public health problem. To date, control strategies have focused on effective diagnostics, mass drug administration, complementary and integrative public health interventions. Non-mammalian intermediate hosts and other vertebrates promote transmission of schistosomiasis and have been utilized as experimental model systems. We discuss the pivotal value of these models in contributing to elimination of schistosomiasis. Experimental animal models that recapitulate schistosomiasis immunology, disease progression and pathology observed in humans are important in testing and validation of control interventions. Treatment of schistosomiasis relies heavily on mass drug administration of praziquantel whose efficacy is comprised due to re-infections and experimental systems have revealed the inability to kill juvenile schistosomes. In terms of diagnosis, nonhuman primate models have demonstrated the low sensitivity of the gold standard Kato Katz smear technique. Antibody assays are valuable tools for evaluating efficacy of candidate vaccines, and sera from graded infection experiments are useful for evaluating diagnostic sensitivity of different targets. Lastly, the presence of schistosomes can compromise the efficacy of vaccines to other infectious diseases and its elimination will benefit control programs of the other diseases. As the focus moves towards schistosomiasis elimination, it will be critical to integrate treatment, diagnostics, novel research tools such as sequencing, improved understanding of disease pathogenesis and utilization of experimental models can assist with evaluating performance of new approaches.